Menggali Perspektif Guru Terhadap Lembar Kerja Siswa (Hard Scaffolding) di Provinsi Lampung: Apakah Implementasinya Dalam Pembelajaran Dapat Meningkatkan Keterampilan HOTS dan Kolaborasi Siswa? - Desi Purwanti; Tri Jalmo; Abdurrahman Abdurrahman; Chansyanah Diawati (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to describe teachers' perceptions of the role of student worksheet (Hard Scaffolding) in improving HOTS and students' collaboration skills. The research was conducted in the province of Lampung, Indonesia, involving 56 science teacher respondents through the MGMP IPA forum (Science Subject Teacher Consultation). The research design is mixed methods. The mixed methods strategy used by Sequential Explanatory Design combines qualitative and quantitative data collection and data analysis. Data was taken using a questionnaire that was distributed using a Google form. The survey results show that teachers have a positive perception of student worksheet (hard scaffolding) to improve students' higher-order thinking skills and collaboration skills. Based on the results of an analysis of the use of student worksheet in schools, most teachers have not used student worksheets that are able to train students to achieve competence optimally. The scaffolding strategy in science learning can help the learning process where students are given some assistance during the early stages of learning and then reduce this assistance and provide opportunities for students or students to take over greater responsibility after being able to do it on their own so as to be able to involve students. actively in a learning process that is oriented to equip students with higher-order thinking skills and collaboration skills.